Kompetensi Pustakawan Dalam Database Scopus Periode 2010 - 2020: Suatu Studi Bibliometrik - Yupi Royani; Rochani Nani Rahayu (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2022)
A study was conducted on the 2010-2020 Scopus data base on librarian competence, with the aim of knowing: a) The growth of scientific publications on the topic of librarian competence from the Scopus data base; b). Core journal growth rankings; c) Researcher productivity; d) Number of publications based on affiliation / institution; e) Number of publications by country; f) Number of publications based on document type; and h) Number of publications by subject. This study was conducted by searching through the Scopus database (http://www.scopus.com). A search on the Scopus database uses the term or the word Librarian Competency, on January 11, 2021, which is contained in the title, abstract and keywords. As for visualizing the development of research on librarian competence, the VOSViewer software is used. The results showed that scientific publications on librarian competency topics for the period 2010-2020 were 280 articles, most of which were from the Journal of the Medical Library Association, with 38 documents. The most productive writers are Zhang, Y. with 4 titles. Most of the documents came from the United States with 106 documents, with the type of journal articles, namely 230 documents, and the most subjects were Social Sciences with 52.90%. When viewed from the bibliometric visualization, six clusters of subjects were found. It is concluded that social science dominates the subject and the United States is the country with the most research on librarian competence.